Etika K3 di Era Digital : Pelatihan Interaktif Berbasis Teknologi untuk Meningkatkan Budaya Keselamatan Kerja - maulana, agus; Abdurrafi, Ahmad; Fhandika, Fhandika; Mokodompit, Eliyanti Agus (Jurnal Mirai Management, 2025)
In this ever-evolving digital age, the use of technology in occupational safety and health training is becoming increasingly important. Technology-based interactive training, which includes the use of virtual simulations, interactive videos, and gamification platforms, can improve the effectiveness and engagement of workers in understanding the safety culture in the workplace. This article examines the importance of applying technology in OSH training to create a safer and more productive work environment based on a literature review. The results of the literature review indicate that technology-based occupational safety and health training has significant potential in enhancing workplace safety culture. Technologies such as virtual simulations, gamification, and e-learning offer more immersive and flexible training experiences.